Late bleeding during anterior approach to the hip: case Report - Scaglia, Marco; Ditta, Alessandro; Magnan, Bruno; Navarro, Ugo; Cassini, Marco (Acta Biomedica Atenei Parmensis, 2019)
Vascular injuries represent an uncommon complication of total hip arthroplasty, with an incidence of 0.1-0.3% as reported in the literature. The aim of the study is the description of a case of late bleeding in a female patient undergoing surgery for total hip arthroplasty in right osteoarthritis through direct anterior approach. The treatment carried out was a selective embolization of the main ascending branch of the lateral circumflex artery. This was performed by placing two spirals following an angiography, which was revealing an active spreading of contrast at the right femoral circumflex ascending artery. The effectiveness of endovascular techniques for the treatment of early and late bleeding after surgery is pointed out.